Analisis Leverage dan Profitabilitas Terhadap Harga Saham Yang Terdaftar di Bursa Efek Indonesia - Elviana Elviana; Vargo Christian L. Tobing (Komunitas Dosen Indonesia, 2022)
This study aims to determine the analysis of leverage and profitability on stock prices listed on Indonesia. Where the population in this study were 26 companies listed on the Indonesia Stock Exchange. This studi using quantitative method. In addition, the sample in this study was 7 companies. The data used in this study is secondary data from financial statements. The data used are data obtained from the 2016-2020 annual report from the official IDX website, namely www.idx.co.id The research method used is quantitative methods such as descriptive statistical analysis, classical assumption test, linear regression analysis. multiple tests, hypothesis testing (t test and f test) and determination test (R2). In this study, the t-test showed that the leverage ratio (debt to equity ratio) partially had no significant effect on stock prices and the profitability ratio (return on equity) partially had no significant effect on stock prices. The f test results show that the leverage ratio (debt to equity ratio) and profitability (return on equity) simultaneously have no significant effect on stock prices. Finally, the coefficient of determination test obtained the percentage of the independent variable on the dependent variable, namely 3,1% and 96.9% influenced by other factors